Simulasi Perdagangan Saham PT Tambang Batubara Bukit Asam, Tbk. dengan Macd dan Williams % Range - Benny Benny; Tomy G. Soemapradja (Bina Nusantara University, 2010)
Moving Average Convergence Divergence (MACD) is a momentum indicator to determine the indication of the trend reversal point. Williams% Range is also a momentum indicator that can provide when reversal trend will occur. This analysis will use the data movement of stock prices for PT Tambang Coal Bukit Asam Tbk. (PTBA). PTBA stock prices are influenced by fundamental conditions such as limited supply of fuel which is rumored and coal is the main alternative fuels other than oil. Study period was 241 trade days. Data are analyzed in several periods and then fitted with the MACD indicator and Williams % R, then simulate the trade during the period of research studies to determine the level of trading profits or losses based on the combination of both these technical indicators. The conclusion of this analysis, the MACD is an indicator that is considered slow (lagging) in giving an indication of weakness, but in reverse the MACD is considered to provide an accurate indication of where the indication given is rarely wrong. Williams% R is an rapid indicator in anticipation of a reversal trend, but these indicators often give a false indication since this indicator is quite sensitive to the movement of stock prices goings go up or down.